Challenging Vaginal Discharge, Lactobacillosis and Cytolytic Vaginitis - Gary Ventolini; Kushal Gandhi; Nathan Joshua Manales; John Garza; Asley Sanchez; Brianna Martinez (Tehran University of Medical Sciences, 2022)
In women's health, clinicians are often faced with diagnosing and administering treatment to patients who present with an increased vaginal discharge without much other information to work with. It's only once a patient's background is reviewed and lab work is completed that two common reasons behind vaginal discharge with similar symptoms, Lactobacillosis and Cytolytic Vaginitis, can be differentiated and a proper diagnosis can be reached. Now, we understand that Lactobacillosis and Cytolytic Vaginitis are symptomatically confused by patients as well as inexperienced clinicians. Lactobacillosis involves the presence of abnormal, extremely long Lactobacilli, a keystone species for vaginal health, while Cytolytic Vaginitis mainly involves, increased Lactobacilli, pH between 3.5 and 4.5, presence of cytolysis, and a lowered white blood cell count. Both present with similar discharge, leading to their conflation. A microscopic examination of the discharge using a wet mount with normal saline can provide 80% diagnostic sensitivity until further testing can be completed.